Stenting venous outflow gives symptomatic improvement in a patient with an inoperable brainstem arteriovenous malformation. (October 2013) - Higgins, J. Nicholas P.; Kirkpatrick, Peter J.
Abstract The extent to which arterial steal or venous hypertension contributes to symptoms in patients with high flow brain arteriovenous malformations (AVMs) is not always clear. We describe a patient with an inoperable AVM of the pons, presenting with headache and neurological deficit where improving venous outflow by stenting produced substantial clinical benefit.